Implementation of point of sales at Kopi Lentera using agile methods and scrum framework - Darmanto, Tedjo; Syaepulloh, Rizal; Rahayu, Ayu Sri; Fauzi, Luthfi Ahmad; Nasrullah, Yusron Fauzan; Ibadurrahman, Gibran Farras (ARKA INSTITUTE, 2024)
Implement Point Of Sales (POS) at Kopi Lentera using Agile and Scrum Framework methods to improve transaction efficiency and accuracy and customer service quality. The purpose of this research is to improve efficiency in the transaction process, reduce errors, and improve customer relations by offering more responsive services through the design of a web-based POS system. The Agile method and Scrum Framework are utilized for managing the development process to ensure speed and adaptability to change. The data collection process is carried out by observation, interview, and literature study. Then the implementation of the device will be tested with the System Usability Scale (SUS) conducted on 10 respondents through a questionnaire. The study concludes that applying the agile-scrum method can result in the development of a POS system that meets the needs with a shorter development time. The implementation results show an increase in the efficiency of recording and transactions, as well as improving the quality of customer service.